2011
DOI: 10.3109/00365521.2011.584899
|View full text |Cite
|
Sign up to set email alerts
|

Improved detectability of small-bowel lesions via capsule endoscopy with computed virtual chromoendoscopy: A pilot study

Abstract: Objective. Real-time video capsule endoscopy (CE) with flexible spectral imaging color enhancement (FICE) improves visibility of small-bowel lesions. This article aims to clarify whether CE-FICE also improves detectability of small-bowel lesions. Patients and methods. A total of 55 patients who underwent CE at Hiroshima University Hospital during the period November 2009 through March 2010 were enrolled in the study. Five patients were excluded from the study because residues and transit delays prevented suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 19 publications
1
51
2
1
Order By: Relevance
“…Imagawa et al [18] have reported that FICE application provided improved image quality of angioectasias, erosion/ulcerations, and various tumours, when FICE wavelength settings 1 and 2 were used. In a more recent pilot study though [19] , the same group found that the detection rate of ulceration/erosion did not differ statistically between conventional i.e., WL-SBCE and FICE-SBCE review.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Imagawa et al [18] have reported that FICE application provided improved image quality of angioectasias, erosion/ulcerations, and various tumours, when FICE wavelength settings 1 and 2 were used. In a more recent pilot study though [19] , the same group found that the detection rate of ulceration/erosion did not differ statistically between conventional i.e., WL-SBCE and FICE-SBCE review.…”
mentioning
confidence: 99%
“…In the remainder (n = 20), the stool specimen for calprotectin was obtained in period of ± 30 d from the SBCE [12] . Interestingly, Imagawa et al [19] also showed that the difference in erosive/ulcerative lesion detection between conventional SBCE and SBCE-FICE (at the various settings) was not statistically significant. This simply means that although chromoendoscopy works well in improving the image quality of captured lesions, it does not lead to improved lesion detection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies aiming to determine the potential utility of FICE virtual chromoendoscopy in small-bowel capsule enteroscopy are even fewer. Imagawa et al (8), in a prospective study, again identified settings 1 and 2 as allowing better identification, mainly of angioectasias. In our case, setting 2 was chose and applied.…”
mentioning
confidence: 99%
“…[40]. Contrast enhancement techniques such as flexible spectral imaging color enhancement (FICE) have been reported to improves detection of angioectasia [41]. Moreover, the new contrast image capsule endoscope (CICE) developed by Olympus medical systems has been shown to improved the visibility of minute structures of adenomatous polyps [42].…”
Section: Applicability the Proposed Methods And Computational Costmentioning
confidence: 99%